Ragam Bahasa dalam Interaksi Sosial di Desa Bonto Tala, Kecamatan Pattallassang, Kabupaten Takalar - Muhammad Dahlan; Hanana Muliana; Nurfausiah Nurfausiah (STIKes Ibnu Sina Ajibarang, 2024)
The aim of this research is to explain the forms of language variation used and describe the factors that influence language variation in children's social interactions in BontoTala, Pattallassang District, Takalar Regency. This type of research is qualitative descriptive research which uses data and data sources. The data in this research are variations in the language of children's social interactions in Bonto Tala, Pattallassang District, Takalar Regency and the data source is 20 children taken in BontoTala, Pattallassang District, Takalar Regency. This study included 12 male and female children and 8 female children aged 7-9 years. The results of this research show the forms of language variation used by children in Bonto Tala, Pattallassang District, Takalar Regency. The use of language variations, namely language variations in terms of speakers, language variations in terms of usage, language variations in terms of formality and language variations in terms of means. Factors that influence language variations in children's social interactions in Bonto Tala, Pattallassang District, Takalar Regency. Using language variations is an environmental factor, social status and age factor.